Արաբ-իսրայելական թնջուկը և հակամարտության կարգավորման ամերիկյան մոտեցումների փոխակերպումը. «Դարի գործարք» - Արզումանյան, Անահիտ («Զանգակ - 97»)
The paper deals with the disagreements around the settlement of the key issues of the Arab-Israeli conflict and the realities formed by the new position of the main actor in the peace process - the United States. The pro-Israeli policy decisions and biased approach to the settlement of the conflict of the former President of the United States Donald Trump’s administration are projected on the issues of the occupied territories, Palestinian refugees, the status of Jerusalem and the independent Palestinian state, which establishes a new political reality. As a result, the legal rights of Palestinians are being violated in terms of having an independent state. Accordingly, the lack of a solution to the Arab-Israeli conflict casts doubt on the possibility of "peaceful coexistence of the two nations" and creates favorable conditions for new clashes between the conflicting parties, because the diplomacy of the United States as the main actor of the peace process, which doesn’t currently have the prerequisites for the resolving of the conflict. As a result, the existing security problems in the region remain unresolved, which also poses a challenge to international peace and stability.
Keywords: Պատմություն; Քաղաքականություն